Analisis Strategi Keberlanjutan pada Perusahaan Unilever - Baginda, Ariq Naufal; Fauzi, Achmad; Yulius Caesar, Leo Andri; Iswanto Putra, Anthony Widjaja; Aadilah Atriliano, Rafi; Larasati, Saskia; Nur Utami, Salma (Jurnal Ilmu Manajemen Terapan, 2024)
In this research, we will discuss a case study analysis of the implementation of sustainability strategies in Unilever. As a "Fast Moving Consumer Goods" company, Unilever has a social and environmental responsibility and has adopted innovation and sustainable services in its business strategy. Researchers will discuss the concept of sustainability and its implementation strategies at PT. Unilever, as well as how the impact of sustainability itself is related to the industrial sector. This analysis will cover the development of products, processes and services offered by the company, as well as how international factors influence sustainable business policies and practices.